Health literacy, health empowerment and health information search in the field of MMR vaccination: a cross-sectional study protocol. Issue 6 (19th November 2012) - Diviani, Nicola; Camerini, Anne-Linda; Reinholz, Danuta; Galfetti, Alessandra; Schulz, Peter J
Abstract : Objectives: Although public health offices have a detailed record of the vaccination coverage among adolescents in Switzerland, little is known about the factors that determine the decisions of parents to get their children vaccinated. Based on Schulz & Nakamoto's Extended Health Empowerment Model, the present study aims at surveying parents of adolescents in Ticino (Switzerland) to get insights into the role of health literacy, health empowerment, information search behaviour and potential confounding variables that influence whether adolescents are not at all vaccinated, undervaccinated or fully covered against measles, mumps and rubella (MMR). Methods and analysis: A survey including concepts of the Extended Health Empowerment Model will be administered to all families with adolescents attending the third year of middle school in Ticino. Subsequently, survey responses will be matched with actual data on MMR vaccination coverage of adolescents collected from the Cantonal Office of Public Health in Ticino. Discussion: The results of this study will allow one to draw more comprehensive conclusions about the factors that play a role in parents' decisions regarding the vaccination of their children. At the same time, the study will provide useful insights on which are the main issues to be considered when addressing parents (on an interpersonal as well as a mass communication level) regarding the vaccination of their children.